2020
DOI: 10.1016/j.jsps.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of non-alkaloid natural compounds of Angelica purpurascens (Avé-Lall.) Gilli. (Apiaceae) with cholinesterase and carbonic anhydrase inhibition potential

Abstract: In current study is done antioxidant, anticholinesterase, and carbonic anhydrase isoenzymes I and II inhibition assays, screening of biological active compounds and electronic microscopy analysis of secretory canals of fruits, flowers, roots, and aerial parts extracts and essential oils of Angelica purpurascens. Phenolic constituents, antioxidant, and anti-lipid peroxidation potentials of variants were estimated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and thiobarbituric acid (TBA) processes. Cholinesterase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 65 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…Coumarins constitute another important class of cholinesterase inhibitors as seen in some scientific reports [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Compounds 1 – 6 ( Table S3 ) isolated from Angelica archangelica , Caryopteris odorata , and Mutellina purpurea showed low activities, and although with slight structural differences, there is no significant difference in their activities [ 86 , 87 , 88 , 89 ]. Between compounds 6 and 7 , the addition of a prenyl group decreases the percentage inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Coumarins constitute another important class of cholinesterase inhibitors as seen in some scientific reports [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Compounds 1 – 6 ( Table S3 ) isolated from Angelica archangelica , Caryopteris odorata , and Mutellina purpurea showed low activities, and although with slight structural differences, there is no significant difference in their activities [ 86 , 87 , 88 , 89 ]. Between compounds 6 and 7 , the addition of a prenyl group decreases the percentage inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hydroxyl groups of verbascoside exhibited seven hydrogen bondings with the oxygen atoms of the amino acids His67, Asn69, Gln92, Ser197, and Thr199. 1.008 0.9935 0.222 0.9943 0.734 0.12 0.159 0.04 a) Acetazolamide was used as a standard inhibitor for both hCA I, and II, and taken from reference of the previous study 43) . When hCA II docking results of the compounds were evaluated, it was seen that verbascoside had lower energy score 10.08 kcal/mol than oleuropein 8.58 kcal/mol .…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…OP has been isolated from the root EtOAc fraction of A. koreana [ 37 ], as well as from the methanolic and CH 2 Cl 2 soluble partitions of A. pancicii by utilizing flash chromatography (FC) and HPLC [ 38 ]. The fruit part of A. purpurascens has been extracted via various organic solvents, and the NHEX fraction was subsequently subjected to CC on silica gel, leading to OP purification [ 39 ].…”
Section: Phytochemical Studies Of Oxypeucedaninmentioning
confidence: 99%
“…In another study, OP indicated a weak anti-AChE activity, with an IC 50 of 69.3 ± 1.1 µg/mL, while eserine had an IC 50 of 0.51 ± 0.03 µg/mL as the positive control [ 19 ]. Moreover, by utilizing the Ellman method, OP revealed the strongest AChE (19.36 ± 1.87%) and BChE (butyrylcholinesterase enzyme, 36.89 ± 1.23%) inhibitory effects among the compounds isolated from Angelica purpurascens, including stigmasterol, β-sitosterol, and bergapten [ 39 ].…”
Section: Biological Activities Of Oxypeucedaninmentioning
confidence: 99%
See 1 more Smart Citation